No frequency change of prehospital treatments by emergency medical services providers for traumatic cardiac arrest patients before and after the COVID-19 pandemic in Korea: an observational study - Ju Heon Lee; Hyung Il Kim (Journal of Trauma and Injury)
Purpose Out-of-hospital traumatic cardiac arrest (TCA) often has a poor prognosis despite rescue efforts. Although the incidence and mortality of out-of-hospital cardiac arrest have increased, bystander cardiopulmonary resuscitation (CPR) has decreased in some countries during the COVID-19 pandemic. In the prehospital setting, immediate treatment of cardiac arrest is required without knowing the patient’s COVID-19 status. Because COVID-19 is usually transmitted through the respiratory tract, airway management can put medical personnel at risk for infection. This study explored whether on-scene treatments involving CPR for TCA patients changed during the COVID-19 pandemic in Korea. Methods This retrospective study used data from emergency medical services (EMS) run sheets in Gangwon Province from January 2019 to December 2021. Patients whose initial problem was cardiac arrest and who received CPR were included. Data in 2019 were classified as pre–COVID-19 and all subsequent data (from 2020 and 2021) as post–COVID-19. Age, sex, possible cause of cardiac arrest, and treatments including airway maneuvers, oropharyngeal airway (OPA) or i-gel insertion, endotracheal intubation (ETI), bag-valve mask (BVM) ventilation, intravenous (IV) line establishment, neck collar application, and wound dressing with hemostasis were investigated. Results During the study period, 2,007 patients received CPR, of whom 596 patients had TCA and 367 had disease-origin cardiac arrest (DCA). Among the patients with TCA, 192 (32.2%) were pre–COVID-19 and 404 (67.8%) were post–COVID-19. In the TCA group, prehospital treatments did not decrease. The average frequencies were 59.7% for airway maneuvers, 47.5% for OPA, 57.4% for BVM, and 51.3% for neck collar application. The rates of ETI, i-gel insertion, and IV-line establishment increased. The treatment rate for TCA was significantly higher than that for DCA. Conclusions Prehospital treatments by EMS workers for patients with TCA did not decrease during the COVID-19 pandemic. Instead, the rates of ETI, i-gel insertion, and IV-line establishment increased.